Innovator ranibizumab ComparEd to Biosimilar ranibizumab in combination with Expansile gas in submaculaR HemorrhaGe: the ICEBERG study - Debdulal Chakraborty; Tushar Kanti Sinha; Soumen Mondal; Subhendu Boral; Arnab Das; Saptorshi Majumbar; Angshuman Mukherjee; Ranabir Bhattacharya; Sumit Randhir Singh (BMC Ophthalmology)
Abstract Purpose To compare the anatomical and visual outcomes in eyes with submacular hemorrhage (SMH) treated with a combination of ranibizumab (RBZ) either innovator or biosimilar (Razumab) and intravitreal perfluoropropane gas (C3F8). Methods Treatment naïve neovascular age related macular degeneration (n-AMD) patients with SMH were retrospectively analyzed. Patients received either innovator or biosimilar RBZ (3 loading doses followed by pro re nata regimen) and single injection of intravitreal C3F8. Optical coherence tomography (OCT) was performed at baseline, 1, 3 and 6 months. Changes in best corrected visual acuity (BCVA) and central macular thickness (CMT) were assessed at 6 months. P value ≤ 0.05 was considered statistically significant. Results A total of 67 eyes (35 and 32 eyes in innovator and biosimilar group respectively) were analyzed. BCVA improved from 1.15 ± 0.19 to 0.51 ± 0.23 logarithm of minimum angle of resolution (logMAR) in innovator RBZ group (p < 0.001) and from 1.17 ± 0.15 to 0.53 ± 0.20 logMAR in biosimilar RBZ group (p < 0.001). Similarly, mean CMT showed significant reduction in both groups at 6 months (innovator RBZ: 609.5 ± 50.1 μm to 254.3 ± 20.3 μm, p < 0.001; biosimilar RBZ: 602.3 ± 58.9 μm to 251.8 ± 22.3 μm, p < 0.001). Intergroup comparisons between innovator and biosimilar RBZ showed no differences in either BCVA or CMT at all time points (all p values > 0.05). Mean number of intravitreal injections was marginally higher in innovator group compared to biosimilar RBZ (4.37 ± 0.49 vs. 4.22 ± 0.42; p = 0.18). Conclusion Biosimilar RBZ may act as a viable alternative to innovator RBZ to treat SMH with comparable anatomical and visual outcomes at 6 months.